Peranan Hasil Laboratorium Forensik Sebagai Bukti Dalam Tindak Pidana Narkotika Di Badan Narkotika Nasional Kabupaten Gianyar - I Gusti Ngurah Wira Sanjaya; I Nyoman Gede Sugiartha; I Nyoman Sutama (Warmadewa Press, 2022)
The rapid development with sophisticated technology has resulted in narcotics criminals becoming more skilled in drug abuse. The process of proving narcotics must be proven with strong evidence, one of which must refer to the Criminal Procedure Code which is regulated in Article 184 paragraph (1) letter c, namely an authentic letter in determining the judge's belief regarding expert testimony, in this case written statements. This research aims to examine the form of the role of forensic laboratory results as evidence in narcotics crimes at the National Narcotics Agency (BNN) of Gianyar Regency. The research method used in this research is the empirical method. Researchers use legal research methods with a sociological juridical approach. Sources of data used in this research are primary data and secondary data. The data that has been collected was analyzed using qualitative methods. From the data analysis data, this research shows that the results of the forensic laboratory can be used as evidence to strengthen the demands to believe that the judge of a criminal act for the perpetrator has played a very important role in helping investigators find the elements of the crime they committed.